2019
DOI: 10.1111/1440-1630.12575
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy intervention addressing weight gain and obesity in people with severe mental illness: A scoping review

Abstract: Background: Individuals diagnosed with severe mental illness have higher rates of obesity than the general population due to a range of factors, including: medication side effects, poor nutrition and reduced physical activity. Obesity is associated with increased mortality and reduced quality of life. Evidence suggests that lifestyle interventions can be effective in addressing this issue. While such interventions would appear to fit within the scope of practice of occupational therapy, there is no publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…These different approaches may also reflect the participants' primary caseload. For instance, within a mental health setting, occupational therapists frequently contribute to lifestyle interventions to address weight gain and obesity (Conn et al, 2019; Haracz et al, 2013; Mahony et al, 2012). However, occupational therapists feel unprepared by their entry‐level education to provide these interventions (Mahony et al, 2012) and experience a tension between providing occupation‐focused intervention, such as shopping, meal planning, and meal preparation, and providing specific dietary or nutrition advice (Conn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These different approaches may also reflect the participants' primary caseload. For instance, within a mental health setting, occupational therapists frequently contribute to lifestyle interventions to address weight gain and obesity (Conn et al, 2019; Haracz et al, 2013; Mahony et al, 2012). However, occupational therapists feel unprepared by their entry‐level education to provide these interventions (Mahony et al, 2012) and experience a tension between providing occupation‐focused intervention, such as shopping, meal planning, and meal preparation, and providing specific dietary or nutrition advice (Conn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Participants worked in a variety of settings. However, only a small number worked in mental health or rural settings, despite these populations being more likely to be of higher weight than the general population (AIHW, 2017; Conn et al, 2019). Not all Australian states and territories were represented.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted based on limited research. A scoping review was performed through the methodology proposed by Arksey and O'Malley (8,9). This review was done in 5 stages:…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Arbesman and Logsdon 13 carried out a systematic review in which they described a greater involvement in education and employment of people with SMI who were intervened with OT focused on social participation. Similarly, Conn et al 14 showed OT to be a key intervention for weight loss in people with SMI, improving their motivation and helping them to acquire healthy lifestyles.…”
Section: Introductionmentioning
confidence: 98%